Line transect estimates of Irrawaddy dolphin abundance along the eastern Gulf Coast of Thailand - Hines, Ellen; Strindberg, Samantha; Junchompoo, Chalatip; Ponnampalam, Lousa S.; Ilangakoon, Anoukchika D.; Jackson-Ricketts, Justine; Mananunsap, Somchai (Frontiers in Marine Science, 2015)
Effective conservation of coastal marine mammals is largely dependent on reliable knowledge of their abundance, as well as the ecological and human factors driving their distribution. In developing countries, lack of resources and capacity frequently impedes research needed to estimate abundance and to determine the ecological requirements of coastal marine mammals and the impact of threats related to coastal development and fisheries. Over the course of five years, we developed practical research methods and trained local scientists in Thailand to use accepted line transect distance sampling methods for abundance assessment. The study focused on a little-known coastal and freshwater species found throughout Southeast Asia, namely the Irrawaddy dolphin, which has been sighted regularly along the coast of the eastern Gulf of Thailand. During five years of line transect boat surveys in Trat Province, the eastern-most province in Thailand, we found an average of 423 dolphins distributed within 12km of the coast. Compared to other abundance estimates of coastal Irrawaddy dolphins in Southeast Asia, this is a relatively large number. This population could extend into the northern coast of Cambodia, where surveys are currently being planned. The Thai government has begun talks with Cambodia about a transboundary marine protected area that would include areas in both countries where coastal Irrawaddy dolphins are found. Other analyses include photo-identification, modeling environmental factors that determine presence, determination of fresh vs. salt water foraging using stable isotopes, and an assessment of threats. Collaboration between scientists in Thailand, Cambodia and Vietnam is further needed to determine dolphin movement and habitat use across borders.